Jejak Wahabi di Nusantara: Pengaruh dan Dampaknya - Udin, Ahmad Irfan (Maliki Interdisciplinary Journal, 2024)
This study discusses the Wahhabi movement or known as muwahhidin, a movement to purify monotheism that invites Muslims to stay away from practices that have the potential to cause polytheism. This movement has an exclusive and rigid character, only referring to the Quran and hadith, and rejecting the truth from non-Islamic sources including local culture and wisdom. In its preaching, Wahhabism emphasizes the principles of reproduction that do not accommodate local wisdom if it is considered contrary to Islamic values. The approach taken by Wahhabi scholars and activists tends to be harsh and insensitive to the feelings of the local community. This often leads to confrontation if practices are found that are considered not in accordance with Islamic teachings according to the Wahhabi version. Indonesia, as a pluralistic country, has a variety of cultures, religions, ethnicities, and languages ​​that grow in the spirit of "Bhinneka Tunggal Ika," which is different but still one. This diversity reflects the unity of the nation based on Pancasila with the principle of Belief in the One Almighty God, where every citizen is required to embrace a religion even though they have different beliefs. This study attempts to examine how the Wahhabism movement with its rigid purification approach interacts in the context of cultural and religious diversity in Indonesia.